Creation and resistance evaluation of a new soybean germplasm rich in betalain - Bi, Yuwei; Zhang, Qi; He, Yun; Ding, Yi; Tian, Haoran; Zeng, Fan; Lyu, Kaidi; Li, Haiyun; Lyu, Shanhua; Fan, Yinglun (Frontiers in Plant Science, 2026)
The betalain biosynthesis system (RUBY) exhibits a stable cross-species coloration advantage in plant genetic transformation. As a visually detectable genetic marker (visible to the naked eye), the color marker holds enormous application potential in positive selection of transgenic plants, identification of hybrids between different plant varieties, haploid selection, and other research. However, when applying the RUBY to plant-microbe interaction research, it is necessary to clarify whether the biosynthesis of betalain and its accumulation in plant tissues and organs alter the plant-microbe interaction processes, including symbiotic or antagonistic relationships. In this study, RUBY transgenic soybean was created. There were no significant differences in nodule number, fresh weight, and dry weight of nodule between the RUBY transgenic line and wildtype soybean after inoculation with Bradyrhizobium japonicum. The biosynthesis and accumulation of betalain did not affect the infection and colonization of rhizobia. The RUBY transgenic line and wildtype soybean were inoculated with Phomopsis longicolla. The results showed that the biosynthesis and accumulation of betalain did not alter the infection and spread of P. longicolla. In field experiments, investigations found that the number of adult brown planthoppers and their eggs attached to the leaves of the RUBY transgenic line was extremely significantly lower than that of the wildtype soybean. This indicates that betalain accumulation may endow soybean with a repellent effect against herbivorous insects. This work revealed that the heterologous biosynthesis and accumulation of betalain in soybean neither affect the nodulation ability of soybean with rhizobia, nor interfere with the infection of soybean by pathogenic bacteria, but also reduce the damage caused by brown planthoppers to soybean. Analysis of the field investigation data on agronomic traits indicated that transgenic soybeans with low betalain content, exerted no adverse effects. In contrast, the transgenic soybean with high betalain content, exhibited negative impacts on node number on main stem, plant height, and yield.